2021
DOI: 10.1177/13634615211001701
|View full text |Cite
|
Sign up to set email alerts
|

Walking Corpse Syndrome: A trauma-related idiom of distress amongst Sri Lankan Tamils

Abstract: This article introduces Walking Corpse Syndrome, a common idiom of distress in Tamil Sri Lanka that is characterized by a variety of cognitive difficulties, feelings that an individual is functioning reflexively or impulsively, and acute attacks of dissociation that are accompanied with the sensation of empty-headedness. Walking Corpse Syndrome demonstrates some overlap with Western nosology, although it appears to be its own unique illness category, most likely of Ayurvedic provenance. The article comprises t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Hagengimana et al (2003) indicated that 35% of the sample studied met the criteria for the panic attack known as ihahamuka and that, among them, rates of PTSD, depression, and somatoform disorders were significantly higher. Recent studies in Sri Lanka (Affleck et al, 2022) have shown that Walking Corpse Syndrome is typically related to depression and PTSD, but it is a distinct syndrome specific to war victims in Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hagengimana et al (2003) indicated that 35% of the sample studied met the criteria for the panic attack known as ihahamuka and that, among them, rates of PTSD, depression, and somatoform disorders were significantly higher. Recent studies in Sri Lanka (Affleck et al, 2022) have shown that Walking Corpse Syndrome is typically related to depression and PTSD, but it is a distinct syndrome specific to war victims in Sri Lanka.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies with 607 participants from a convenience sample, of whom 65.4% (n = 393) were female, were conducted to examine trauma-related cultural syndromes. Three studies were quantitative cross-sectional studies using a self-report questionnaire to collect data (Hagengimana et al, 2003;Hinton et al, 2006Hinton et al, , 2010, while two studies were qualitative (Affleck et al, 2022;Chhim, 2013). Study participants were adult trauma survivors with no comparison group, and participant ages ranged from 18 to 60 years.…”
Section: Study Descriptionsmentioning
confidence: 99%
“…On the other hand, paying credence to both cultural and idiosyncratic of idioms of distress is extremely useful when establishing rapport with patients, and gaining a sense of conflict and support in their lifeworld. It is also useful in developing culturally sensitive therapeutic interventions that enable consensual treatment negotiation (Affleck et al, 2021; Hinton & Lewis-Fernández, 2010). At issue is how local idioms of distress can be identified given that they can take myriad forms ranging from the mundane to the exotic, may be used more or less frequently by different subgroups within the same society, and can change in use over time.…”
Section: Contribution Of Idioms Of Distress To Cultural Psychiatrymentioning
confidence: 99%
“…In India for example, this condition is treated as a humoral disorder by ayurvedic practitioners. In Sri Lanka, rumination related to the trauma of wartime is linked to heat in the body and treated by cold water baths (Affleck et al, 2021). 4.…”
Section: Orcid Idmentioning
confidence: 99%
“…Across stakeholder groups, people identified a core set of symptoms such as thinking too much, anger, and immediate physical health impacts like palpitations and headaches, as well as longer-term harms to physical and social health in school and other group settings. Similarly, Affleck et al (2022) report two parallel studies of Walking Corpse Syndrome among conflict-exposed Tamil Sri Lankans: one focused on the individual lived experiences of this trauma response syndrome and the second examined psychiatrists' perceptions of it among their patients. Like the Figge articles, clinician perception and individual lived experience of the syndrome converged around a common core set of symptoms, though compared to patients, psychiatrists focused on more technical and clinical categorization, as well as root causes.…”
mentioning
confidence: 99%